2022
DOI: 10.1093/rap/rkac006
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depressive symptoms in Japanese women with rheumatoid arthritis

Abstract: Objectives It has been suggested that patients with rheumatoid arthritis (RA) are more likely to suffer from depression. Therefore, this study identified the factors associated with depressive states in female RA patients to inform future patient care. Methods A self-assessment questionnaire was administered to 150 female RA patients aged 20 years and older regarding their satisfaction with disease activity, pain (measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…According to McQuillan et al ( 2022 ), RA functional disability is more strongly associated with depression in males than in females. Depressive symptoms in female patients appear to be more closely related to poor sleep quality or family pressure (Hughes et al, 2021 ; Hamasaki et al, 2022 ).…”
Section: What Causes Depression In Ra Patients?mentioning
confidence: 99%
“…According to McQuillan et al ( 2022 ), RA functional disability is more strongly associated with depression in males than in females. Depressive symptoms in female patients appear to be more closely related to poor sleep quality or family pressure (Hughes et al, 2021 ; Hamasaki et al, 2022 ).…”
Section: What Causes Depression In Ra Patients?mentioning
confidence: 99%
“… 12 Factors such as difficulties in daily life, self-confidence in coping with stress, and expected health status are associated with depression in rheumatoid arthritis (RA) patients. 13 In another study, there has been reported a relationship between poor sleep quality and anxiety, depression, self-efficacy, and stigma in RA patients. 14 Here, sleep disturbance was found to be positively correlated with age, pain, disease activity, depression, anxiety, and stigma, while self-efficacy was negatively correlated with sleep disturbance.…”
Section: Introductionmentioning
confidence: 96%